Kings, Treasures, and Looting: The Evolution of Sovereign Immunity and the Foreign Sovereign Immunities Act - Amineddoleh, Leila A. (The Columbia Journal of Law & the Arts, 2023)
Last year witnessed the conclusion of a long-fought dispute between a private party and a foreign government over an art collection with significant cultural value. It involved a treasure of ecclesiastical objects dating back to Medieval Germany that had once belonged to the royal House of Guelph and housed in the muralled medieval Brunswick Cathedral in Braunschweig, Germany. Ultimately, after over a decade of fighting, the controversy’s resolution did not involve an ownership determination by a U.S. court. Rather, the high court abstained from making a determination and instead declined to exercise jurisdiction over Germany. The lack of decision was not surprising, particularly in light of delicate foreign policy issues at play and the importance of keeping the judiciary out of international political disputes. The court’s unanimous decision was consistent with prior holdings, and so perhaps it was foreseeable that the court did not examine the merits of the ownership claims. However, a line of cases against Greece, Switzerland, and Italy did come as a shock, because they involved claims against foreign countries for asserting ownership interests in antiquities that were suspected of having been looted. Never before had governments been sued for their actions regulating the antiquities market and working to protect cultural artifacts.